Comparison of bacterial microleakage of three bioactive endodontic sealers in simulated underwater diving and aviation conditions - Mehdi Dastorani; Behnam Malekpour; Mohsen AminSobhani; Mohammadsadegh Alemrajabi; Arezoo Mahdian; Behrooz Malekpour (BMC, 2021)
Abstract Background Bacterial microleakage is an important cause of apical periodontitis and endodontic treatment failure. This study aimed to assess the bacterial microleakage of nano-mineral trioxide aggregate (nano-MTA) as a sealer, Endoseal MTA, and GuttaFlow Bioseal sealers in atmospheric pressure, and simulated underwater diving and aviation conditions. Methods In this in vitro, experimental study, 180 extracted single-rooted teeth were cleaned and shaped, and were then randomly divided into three groups for single-cone obturation using Endoseal MTA, GuttaFlow Bioseal, or nano-MTA as a sealer. Each group was then randomly divided into three subgroups, and subjected to ambient atmospheric pressure, 2 atm pressure (to simulate underwater diving), and 0.5 atm pressure (to simulate aviation) using a custom-made pressure chamber. The teeth then underwent microbial leakage test using Streptococcus mutans (S. mutans), and the percentage of samples showing microleakage was recorded for up to 1 month, and analyzed using the Chi-square test. Results The three sealer groups were significantly different regarding bacterial microleakage (P < 0.05). The nano-MTA group showed significantly higher microleakage after 15 days than the other two groups (P = 0.006). The effect of pressure on bacterial microleakage was not significant in any sealer group (P > 0.05). Conclusion Within the limitations of this in vitro study, it may be concluded that single-cone obturation technique using nano-MTA as a sealer results in lower resistance to bacterial microleakage compared with the use of GuttaFlow Bioseal, and Endoseal MTA. Pressure changes in simulated underwater diving and aviation conditions had no significant effect on bacterial microleakage. Trial Registration Number This is not a human subject research.